Sharia Supervisory Board in Limited Company-Based Sharia Banks - Nurhasanah, Nurhasanah (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2022)
Abstract. This paper aims to examine the function of the Sharia Supervisory Board (SSB) due to the inconsistency of laws and regulations concerning this body. Law No. 21 of 2008 on Sharia Banking has required every Sharia Bank and Sharia Business Unit in the Banks to form an SSB. However, Law No. 40 of 2007 on Limited Liability Companies has not regulated the SSB as a corporate organ. This paper analyzes laws and regulations on the SSB and court decisions on cases resulting from legal inconsistencies, with the organizational structure and fiduciary duty theories as analytical frameworks. This study finds out that legal ambiguity results in the absence of coordination between the SSB and other bodies in the organization. Thus, this prevents the SSB from optimally carrying out its functions and roles. Among the consequences is the inability to ensure sharia compliance in business contracts leading to lawsuits to cancel the contracts.Abstrak. Penelitian ini bertujuan menganalisis posisi Dewan Pengawas Syariah (DPS) di tengah inkonsistensi peraturan terkait dengan lembaga tersebut. UU No. 21 Tahun 2008 tentang Perbankan Syariah telah mewajibkan setiap Bank Syariah dan Unit Usaha Syariah pada Bank untuk membentuk DPS. Namun, UU No. 40 Tahun 2007 tentang Perseroan Terbatas tidak mengatur DPS sebagai organ perusahaan. Studi ini mengkaji berbagai peraturan tentang kedudukan DPS dan putusan pengadilan yang menunjukkan konsekuesi dari inkosistensi undang-undang tentang DPS, dengan menggunakan teori struktur organisasi dan fiduciary duty. Kajian ini menemukan bahwa inkonsistensi undang-undang membuat DPS tidak memiliki garis koordinasi dengan organ lain dalam organisasi bank dan tidak dapat sepenuhnya menjalankan fungsi dan perannya. Konsekuensinya adalah fungsi pengawasan tidak optimal, sehingga muncul tuntutan hukum untuk membatalkan kontrak yang dianggap tidak sesuai syariah.